The Incidence and Characteristics of Perinatal Stroke in Beijing: A Multicenter Study - Xia, Qianqian; Yang, Zhao; Xie, Yao; Zhu, Ying; Yang, Zixin; Hei, Mingyan; Ding, Yingxue; Kong, Weijing; Kang, Limin; Yang, Shengnan; Mei, Yabo; Feng, Zhichun; et al. (Frontiers in Public Health, 2022)
Object The incidence of neonatal stroke in Beijing was calculated. Risk factors and clinical characteristics of neonatal stroke were analyzed. Methods It was a multicenter prospective study, including all live births from 17 representative maternal delivery hospitals in Beijing from March 1st, 2019 to February 29th, 2020. The neonates with stroke were assigned into case group. Clinical data were collected, including general information, clinical manifestations and risk factors. The neonates were under routinely follow-ups to 18 months after birth by ASQ and/or Bayley scale assessment. All data were statistically analyzed. Outcomes A total of 27 cases were collected, and the incidence of neonatal stroke in Beijing was 1/2,660, including 1/5,985 for ischemic stroke and 1/4788 for hemorrhagic stroke. There were 17 cases (62.96%) of acute symptomatic stroke, and convulsion within 72 hours was the most common presentation (10 cases, 37.04%). 10 patients had no neurological symptoms and were found by routine cranial ultrasonography due to non-neurological diseases. Risk factors include primiparity, placental abruption/acute chorioamnionitis, intrauterine distress, asphyxia, and severe infection. In the case group, 11.1% (3/27) had poor neurodevelopmental outcomes. Patients had lower scores than those in the control group in communication, gross motor and fine motor scores of ASQ. Conclusion The incidence of neonatal stroke in Beijing is consistent with those in other countries. Routine neuroimaging for infants with risk factors may detect more patients with asymptomatic stroke. Patients with stroke may have neurological sequelae, so early detection, treatment and regular follow-up, are beneficial for the improvement of outcomes.